Role of Polysomnography in the Development of an Algorithm for Planning Tracheostomy Decannulation. (23rd August 2013) - Mehta, Deepak; Robison, Jacob G.; Greenberg, Laura; Maguire, Raymond; Simons, Jeffrey P.
Abstract : Objectives: Examine the role of polysomnography (PSG) in helping determine readiness of tracheostomized patients for decannulation. Study design: Retrospective medical record review of pediatric patients who underwent PSG with tracheostomy tube in place with the goal of decannulation. Methods: Thirty‐three tracheostomized patients who underwent PSG from January 2006 to March 2012 were included. Outcome measures were successful decannulation, PSG results, surgical procedures, and medical comorbidities. Results: Of the 33 patients, 23 (69.7%) were decannulated and 10 (30.3%) were not. One (3.0%) patient failed long‐term decannulation. The average apnea‐hypopnea index (AHI) with a capped tracheostomy for those successfully decannulated was 2.75 (range 0.6 to 7.6), while the AHI for those not decannulated was 15.99 (range 3.2 to 62). Factors associated with success or failure to decannulate were assessed and an algorithm was developed to plan for successful decannulation. Laryngotracheal reconstruction was found to be a significant factor in those successfully decannulated. Those who were not decannulated were found to have multiple medical comorbidities and multi‐level airway obstructions. Conclusions: PSG is a useful adjuvant study in the process of determining a patient's readiness for decannulation. Our current algorithm for decannulation includes upper airway endoscopy with identification of levels of obstruction followed by surgical correction of those obstructions; capped PSG to determine patency of airway and help assess lung function; overnight admission for capping trial, with decannulation the following day, if well tolerated.